Semi-Markov-based approach for the analysis of open tandem networks with blocking and truncation - Oniszczuk, Walenty (Zielona Góra: Uniwersytet Zielonogórski)
This paper describes an analytical study of open two-node (tandem) network models with blocking and truncation.
Keywords: two-node network with blocking and truncation; semi-Markov model; Markov exact algorithm